The downside of damage control orthopaedics: a case of open tibial fracture with injury of anterior tibial artery after external fixation stabilization - Sharifudin, Mohd Ariff; Ismail Mansor, Nur Akmal; Mohd Yusof, Nazri; Sulong, Ahmad Fadzli; Ismail, Raffael; Noor Rahin, Mohd. Shahidan; Ayeop, Mohd Adham Shah; Othman, Ahmad Faidzal (2014)
Background: In the setting of severe trauma, placement of external fixation is an expedient and minimally invasive method of temporarily stabilizing fractures. However, the procedure is not without complications. Most complications are related to pins insertion. Case report: We report a case of a 17-year-old man who sustained an open tibial fracture type IIIC. The posterior tibialis pulse of the affected lower limb was not detectable on initial evaluation. Intra-operative exploration revealed an injured posterior tibialis artery with a 3-cm substance loss at the level of the fracture. The dorsalis pedis artery remained palpable and the toes were pink. Ligation of the posterior tibialis artery was decided by the vascular team. A unilateral external fixator was applied to stabilize the fracture. Pins were inserted within the anatomic safe zones for pin placements. However, immediately after surgery, the toes were noted to be pale and the dorsalis pedis artery was no longer detectable even with Doppler ultrasonography. The distal pin was removed and the wound was re-explored. An iatrogenic partial anterior tibial artery cut was noted near the distal pin insertion site. Although the pin causing the iatrogenic arterial injury was placed under direct visualization, the degree of soft tissue injury altered the appearance of the local anatomy. The pin was subsequently revised and both dorsalis pedis and posterior tibialis arteries were reconstructed using the contralateral saphenous venous graft. Perfusion was restored immediately. Conclusion: This case highlights among the hazardous outcome associated with damage control orthopaedics, particularly when the normal local anatomy is altered due to trauma. Neurovascular structures are still at risk despite the establishment of anatomic safe zones for placement of external fixation pins. Careful assessment of external fixator pin placement is crucial to avoiding iatrogenic injury. A thorough vascular examination prior to leaving the operating room is essential while the patient remains in a controlled setting.